Mimosa sobralii (Fabaceae, Mimosoideae), a new tree species endemic to the southern Brazilian highland slopes - Grings, Martin; Ribas, Osmar Dos Santos (Phytotaxa, 2013)
Mimosa sobralii (Fabaceae), a new species of tree endemic to the northern highland slopes of the Brazilian state of Rio Grande do Sul, is described and illustrated. The new species is close to M. bifurca, from which it is set apart by the arborescent habit, yellow flowers and differences in leaflet morphology.